The Hardness of Boride Layer on the S45C Iron (A preliminary study on surface hardening of ferrous material) - Sutrisno S; Bambang Soegijono (Aceh International Journal of Science and Technology, 2012)
Abstract - The property such as microhardness of boridelayer formed on S45C iron was investigated. Boronizing was carried out in a solid medium consisting of nano size powders of 50% B4C as a donor, 45% SiC as a diluent, and 5% KBF4 as an activator treated at the temperature of 10000C for 8 hours. The phases that were formed on the substrate was found as Fe2B and FeB layer that had smooth and flate shape morphology. The hardness of boride layer on S45C was over 2000 HV, while the hardness of untreated S45C iron was about 196,39 HV. Depending on process time and temperature, the depth of boride layer ranges from 25 to 55 μm, leading to a diffusion controlled process.Keywords : Boronization, hard layer, heat treatment, B4C.KBF4.SiC powder, low carbon steel.